PENGEMBANGAN MULTIMEDIA INTERAKTIF TARI JEPIN LANGKAH SIMPANG BAGI SISWA SEKOLAH MENENGAH PERTAMA - Dwi Oktariani, - (2017)
This study aims to produce a software product multimedia learning is feasible to support the learning of dance. This type of research is research development (Research and Development). The implementation of the research includes several stages: initial state analysis or preliminary study, planning or design, development, and testing to determine the effectiveness of the product. Data analysis techniques include qualitative and quantitative analysis. Qualitative data include critics, suggestions, and input from material experts, media, SBK teachers and students who are collected to improve the products developed. Quantitative data in the form of the exposure of questionnaire results data, and the results of product trials to students in the form of grades achieved by students. The results showed that (1) condition analysis and learning potential; (2) development design in the form of: design of interactive multimedia development, material needs, learning simulation, material evaluation, attached samples of material supporters; (3) media development on the media-making aspect of the design result; (4) testing in the form of media implementation to school through test stages SBK teacher validation, interactive multimedia test at SMPN 15 and SMPN 29 Kota Bandung to know the effectiveness of media in learning. The results of this study are broadly generated interactive multimedia development model of Jepin dance Simpang suitable steps implemented for Nusantara dance learning, with good results on testing media experts, content and teachers SBK. With a complete learning classical 85% category and excellent classical absorption of 78% with high category. In the psychomotor domain the average student score is 80, with 89% classical learning completeness classified as very good category and classical absorption of 80% with high category. Not only that the effectiveness is also seen from the results of distributing questionnaires to students about their response to learning using Jepin dance Step Simpang. Affective aspects or student attitudes are also seen from the learning process where students become more responsible, cooperate, and discipline while working on group projects, students also become independent and honest in individual learning using the media. Students also become more motivated to learn art. Penelitian ini bertujuan untuk menghasilkan produk software multimedia pembelajaran yang layak untuk mendukung pembelajaran seni tari. Jenis penelitian ini adalah penelitian pengembangan (Research and Development). Pelaksanaan penelitian meliputi beberapa tahap yaitu : analisis keadaan awal atau studi pendahuluan, perencanaan atau desain, pengembangan, dan pengujian guna mengetahui keefektifitasan produk tersebut. Teknik analisis data meliputi analisis secara kualitatif dan kuantitatif. Data kualitatif berupa kritik, saran, dan masukan dari ahli materi, media, guru SBK dan siswa yang dihimpun untuk memperbaiki produk yang dikembangkan. Data kuantitatif berupa pemaparan data hasil angket, dan hasil uji coba produk terhadap siswa berupa nilai yang dicapai siswa. Hasil penelitian menunjukan bahwa (1) analisis kondisi dan potensi pembelajaran; (2) desain pengembangan berupa : rancangan pembuatan multimedia interaktif, kebutuhan materi, simulasi pembelajaran, evaluasi materi, contoh-contoh terlampir pendukung materi; (3) pengembangan media pada aspek pembuatan media dari hasil desain; (4) pengujian berupa implementasi media ke sekolah melalui tahapan uji validasi guru SBK, uji coba multimedia interaktif di SMPN 15 dan SMPN 29 Kota Bandung guna mengetahui keefektifitasan media dalam pembelajaran. Hasil penelitian ini secara garis besar dihasilkan model pengembangan multimedia interaktif tari Jepin Langkah Simpang yang cocok diimplementasikan untuk pembelajaran tari Nusantara, dengan hasil baik pada pengujian ahli media, konten dan guru SBK. Dengan ketuntasan belajarar klasikal 85% kategori sangat baik dan daya serap klasikal 78% dengan kategori tinggi. Pada ranah psikomotorik rata-rata nilai siswa ialah 80, dengan ketuntasan belajar klasikal sebesar 89% dinyatakan kategori sangat baik dan daya serap klasikal sebesar 80% dengan kategori tinggi. Tidak hanya itu keefektivitas juga dilihat dari hasil penyebaran kuesioner kepada siswa mengenai respon mereka terhadap pembelajaran menggunakan tari Jepin Langkah Simpang. Aspek afektif atau sikap siswa juga terlihat dari proses pembelajaran dimana siswa menjadi lebih bertanggung jawab, bekerja sama, dan disiplin saat mengerjakan project kelompok, siswa juga menjadi mandiri dan jujur dalam pembelajaran individu menggunakan media tersebut. Siswa juga menjadi lebih termotivasi untuk belajar seni.----